BEAT GENERATION AND ALLEN GINSBERG’S POEMS - Amitabh Ranjan Kanu (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2021)
Beat Generation began to emerge in America in late seventies. Allen Ginsberg decided to teach a course on literary history of Beat Generation at Naropa Institute, Boulder, Colorado of United States. He explained in his first lecture about the course which included major works of the writers of 1940s, 1950s and 1960s. He invited Beat writers to visit his classes and speak to the students about their own work. The students worked with William Burroughs, Gregory Corso, Herbert Huncke, Peter Orlovsky, Michael McClure, Roy Bremser, Carl Solomne, Amiri Baraka and many others. The students of his class started study about Beat Generation sitting at the feet of masters of Beat Generation. The Beat Generation was a literary movement. Ginsberg led the movement from the front. He documented the era, preserved the literature and educated the people through his poems. Ginsberg always considered Kerouac to be the greatest writer, Burroughs to be the greatest intellect and Corso to be the most naturally gifted poet of Beat Generation. Jack Kerouac coined the phrase ‘Beat Generation’. It has several meanings. It means openness. It means to emptied out, exhausted and at the same time wide open perceptive and receptive to a vision. Sometime it denotes dark night of the soul. It has a celebrated phrase ‘everything belongs to me because I am poor’. The paper tries to evaluate the literary movement of Beat Generation with special mentioning of Allen Ginsberg’s poems. Keywords: Beat Generation, literary characteristic, poems of Allen Ginsberg